Multiresistant extended-spectrum beta-lactamase-producing Enterobacteriaceae from humans, companion animals and horses in central Hesse, Germany - Schmiedel, Judith; Falgenhauer, Linda; Domann, Eugen; Bauerfeind, Rolf; Prenger-Berninghoff, Ellen; Imirzalioglu, Can; Chakraborty, Trinad; Justus Liebig University Giessen (My University, 2014)
BACKGROUND:Multiresistant Gram-negative bacteria producing extended-spectrum beta-lactamases (ESBLs) are an emerging problem in human and veterinary medicine. This study focused on comparative molecular characterization of beta-lactamase and ESBL-producing Enterobacteriaceae isolates from central Hesse in Germany. Isolates originated from humans, companion animals (dogs and cats) and horses. RESULTS:In this study 153 (83.6%) of the human isolates (n=183) and 163 (91.6%) of the animal isolates (n=178) were confirmed as ESBL producers by PCR and subsequent sequencing of the PCR amplicons. Predominant ESBL subtypes in human and animal samples were CTX-M-15 (49.3%) and CTX-M-1 (25.8%) respectively. Subtype blaCTX-M-2 was found almost exclusively in equine and was absent from human isolates. The carbapenemase OXA-48 was detected in 19 ertapenem-resistant companion animal isolates in this study. The Plasmid-encoded quinolone resistance (PMQR) gene aac(´6)-Ib-cr was the most frequently detected antibiotic- resistance gene present in 27.9% of the human and 36.9% of the animal ciprofloxacin-resistant isolates. Combinations of two or up to six different resistance genes (penicillinases, ESBLs and PMQR) were detected in 70% of all isolates investigated. The most frequent species in this study was Escherichia coli (74%), followed by Klebsiella pneumoniae (17.5%), and Enterobacter cloacae (4.2%). Investigation of Escherichia coli phylogenetic groups revealed underrepresentation of group B2 within the animal isolates. CONCLUSIONS:Isolates from human, companion animals and horses shared several characteristics regarding presence of ESBL, PMQR and combination of different resistance genes. The results indicate active transmission and dissemination of multi-resistant Enterobacteriaceae among human and animal populations.
Keywords: ESBL; Enterobacteriaceae; comparison; human isolates; animal isolates; ddc:610